Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama pada Masa Pandemi Covid-19 - Muhamad Hasan Mafruh; Muhammad Iqbal Fasa; Ahmad Kumedi Ja'far (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The authority to adjudicate sharia economic disputes has absolutely become the authority of the Religious Courts since the issuance of Law No. 3/2006 concerning Amendments to Law No. 7/1989 concerning Religious Courts and strengthened by Law No. 21/2008 concerning Sharia Banking and the Constitutional Court Decision No. 93/PUU-X/2012. Every year, Islamic economic transactions always increase, even though during the pandemic, Islamic banking in Indonesia grows positively. However, the higher and increasing sharia economic transactions in Indonesia, the more disputes that occur. During the current covid-19 pandemic, the government has issued regulations regarding restrictions ranging from PSBB to PPKM. The purpose of this research is to encourage the emergence of sharia economic dispute resolution innovations, especially in the Judiciary during the Covid-19 pandemic without having to violate the Health protocol. This study uses a qualitative descriptive study, which uses literature studies quoted from books and regulations, both laws and other regulations, as well as direct research into the field to see the realities on the ground related to the settlement of sharia economic disputes during the pandemic. The results in this study indicate that the Supreme Court responds quickly to the rules and policies issued by the government by launching an e-court application and investigation (electronic trial). There are many benefits and conveniences that are felt by people seeking justice, especially parties in sharia economic disputes. However, there are still some obstacles experienced by the Religious Courts and justice seekers in electronic proceedings.